A New Load-Transfer Factor to the Slipping Analytical Formulation in Axially Loaded Piles - Kelvin Lo; Erwin Oh; Darren Newell; Choo Yong (Geotechnics, 2022)
The load-transfer factor (<semantics>ζ</semantics>) in the concentric cylinder approach is often used in analytical formulation in axially loaded piles. The factor is a constant value (in a given pile slenderness ratio and soil condition) devised under the elastic and ‘pre-failure’ perfect pile–soil bonding conditions (a non-slip analytical model). Given most numerical methods have already considered the pile–soil slipping in the ‘pre-failure’ stage, the limitations of non-slip analytical models have recently been discussed, and slipping analytical models have been recommended. Therefore, this research aims to investigate the load-transfer factor in slipping analytical models. This paper reviews that the factor in slipping analytical models is only constant in linear elastic and some Gibson soil conditions. Beyond these conditions, the factor varies as the pile-head load increases in some cohesionless soils. Adopting the existing constant factor in slipping analytical models will deviate the load–displacement results, as supported by numerical results. Therefore, a new equation is proposed to the load-transfer factor, and a new analytical method is proposed by varying the load-transfer factor during loading for improvement. Results presented in this paper demonstrate improved load–displacement results.